Mueller Matrix Imaging Optimized by Uniform Illumination - Guo, Wei; Song, Jiawei; Zeng, Nan; Ma, Hui (Frontiers in Physics, 2022)
In this paper, we present a flat-field Mueller matrix imaging system by adding a beam shaping module with two microlens arrays and a Fourier lens on a traditional wide-field Mueller matrix imaging scheme. We firstly use the scalar diffraction theory to explain the homogenization effect of the beam shaping module, and then we analyze error transfer in Mueller polarimetry, demonstrating the advantages of flat-field illumination on noise suppression. Next, by experiments of various samples, we illustrate the superiority of flat-field polarization imaging not only in terms of improving signal-to-noise (SNR) but also in precisely identifying the structural and quantitative differences between various polarization parameters, Δ, δ, and θ. Finally, the experimental comparison on real pathological slices confirms the better application potential of flat-field polarization imaging in pathological diagnosis and tissue characteristic extraction.